1998
DOI: 10.1038/bjc.1998.595
|View full text |Cite
|
Sign up to set email alerts
|

Tau expression in model adenocarcinomas correlates with docetaxel sensitivity in tumour-bearing mice

Abstract: Docetaxel is a new taxoid with clinical activity in breast and lung cancer. Using docetaxel-sensitive and -refractory mammary and pancreatic murine tumours, as well as human-derived neoplasms, we investigated if a determinant of docetaxel sensitivity could be found at the level of its mechanism of action. Because microtubules represent the cellular targets of the drug, we studied their heterogeneity in the tumour models to try to explain the differences in drug sensitivity. Reverse transcription-polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Docetaxel was highly active in vivo against advanced stage pancreatic ductal adenocarcinoma P03 and inactive against early stage P02 (Bissery et al, 1991;Veitia et al, 1998). We showed that the sensitive tumour P03 expresses a higher level of Tau proteins when compared to the docetaxel refractory neoplasm P02 (Veitia et al, 1998). This higher quantity of Tau may increase the sensitivity to the drug since both Tau and docetaxel stabilize microtubules.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…Docetaxel was highly active in vivo against advanced stage pancreatic ductal adenocarcinoma P03 and inactive against early stage P02 (Bissery et al, 1991;Veitia et al, 1998). We showed that the sensitive tumour P03 expresses a higher level of Tau proteins when compared to the docetaxel refractory neoplasm P02 (Veitia et al, 1998). This higher quantity of Tau may increase the sensitivity to the drug since both Tau and docetaxel stabilize microtubules.…”
mentioning
confidence: 62%
“…Anti-MAP2 152 is a monoclonal produced in our laboratory (Kalil et al, 1988;Veitia et al, 1998 Summary We have studied the state of microtubule associated protein 2 (MAP2) in the pancreatic ductal adenocarcinomas P03 and P02 (sensitive and refractory to docetaxel respectively) since they express the corresponding mRNA and MAP2-related peptides. Immunohistochemical localization showed that in tumour P03 the MAP2-related peptides are highly expressed and confined to the epithelial malignant cells while in P02 the intensity of the immunostaining is lower.…”
Section: Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37][38] Expression of tau was observed in tumors including astrocytomas, oligodendrogliomas, chondrosarcomas and gastrointestinal stromal tumors, [39][40][41] and tau phosphorylation is associated with anti-cancer drug sensitivity and drug-induced apoptosis. [42][43][44][45] We and other investigators found that expression of the CKAP2 gene is also upregulated in some human tumors. Because some anti-cancer drugs target microtubule dynamics, the status of MAPs in cells might play a crucial role in determining the drug sensitivity of cancer cells.…”
Section: Discussionmentioning
confidence: 99%